A scientometric analysis of cycling and the case study of the city of Ioannina - Anagnostopoulos Apostolos; Tsompikos Andreas; Kehagia Fotini (E3S Web of Conferences, 2023)
In urban areas, cycling as a sustainable mode of transport contributes to creating more liveable and vibrant urban environments. They take up less space than cars, reduce noise pollution, and create a human-scale, people-friendly atmosphere. This paper provides an environmental and sustainable scan of the literature on bicycles using established systematic literature review approach. The main issues the existing literature is dealing with according to the identified clusters can be categorized into four main categories that rely on environment-oriented, infrastructure-oriented, safety-oriented and health-oriented research fields, where the majority of research has been focused during the analysis period. Moreover, in this study, the implementation and use of cycling in the city of Ioannina is examined. The technical characteristics of the existing cycling paths in the city, the policy and the behavioral aspect of the people are presented by analyzing the responses of 102 residents of Ioannina in a structured questionnaire.